Therapeutics of placenta previa - Bazul, Víctor (2015)
The treatment of placenta previa, before the introduction of cesarean section, abdominal, was based on a series of methods whose purpose was to restrain, reduce or eliminate bleeding. There is no single mode of treatment; good way depends on the variety, the importance of bleeding, their impact on the general state, the state of the cervix integrity, ease of access to the membranes, the degree of infection, the viability of fetus, the time and environment in which they act.